Potensi Konflik Sosial dalam Tradisi Upacara Adat Ma’ Baku-Baku pada Masyarakat Uru di Desa Ledan Kabupaten Enrekang - Citra, Lisa (UNIVERSITAS NEGERI MAKASSAR, 2017)
This study aims to determine (1). The process of the occurrence of social conflicts in the tradition of traditional ceremony Ma 'Baku-Baku in Uru community in Ledan Village Enrekang District. (2). To find out how the forms of social conflict in the tradition of traditional ceremony Ma 'Baku-Baku on Uru community in Ledan Village, Buntu Batu District Enrekang Regency. And (3). To find out how to prevent the occurrence of social conflict in the tradition of Ma 'Baku-Baku traditional ceremony in Uru society in Ledan Village, Buntu Batu Sub-district, Enrekang Regency. The data collection with the method of observation, interview, and documentation, while the analysis used in this research is descriptive qualitative. The results of this study indicate that there are six processes of conflict in the tradition tradition ceremony Ma 'Baku-Baku in Uru first society that is the arrival of Islamic organizations in Uru, both technological advances, the third the existence of high education, the fourth because the tradition began to slowly abandoned, and the fifth is the effort to eliminate the tradition of traditional ceremonies Ma 'Baku-Baku and the last is the effort to maintain the tradition. Then there are four forms of social conflict that occurred in the first Uru society that is conflict between families, the two conflicts between groups, the three social conflicts, the fourth is political conflict. And in this study found four government efforts in preventing the first conflict that is, mutual respect, strengthening family relationsships, more concerned with the group than the self, and be respectful.